2005
DOI: 10.1086/432030
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Chromospheric Brightenings beneath a Transequatorial Halo Coronal Mass Ejection

Abstract: Analyses of multiwavelength data sets for a solar eruption at $21:30 UT on 2002 December 19 show evidence for the disappearance of a large-scale, transequatorial coronal loop ( TL). In addition, coronal manifestations of the eruption ( based on SOHO EIT and LASCO images) include large-scale coronal dimming, flares in each associated active region in the northern and southern hemispheres, and a halo CME. We present detailed observations of the chromospheric aspects of this event based on H images obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 29 publications
12
50
1
Order By: Relevance
“…Analogous behavior in which eruptions involve structures located outside of strong/complex fields and their associated flares occurs for CMEs originating in transequatorial loops. Such events have been reported by Khan & Hudson (2002) and Balasubramaniam et al (2005).…”
Section: Summary and Interpretationsupporting
confidence: 61%
“…Analogous behavior in which eruptions involve structures located outside of strong/complex fields and their associated flares occurs for CMEs originating in transequatorial loops. Such events have been reported by Khan & Hudson (2002) and Balasubramaniam et al (2005).…”
Section: Summary and Interpretationsupporting
confidence: 61%
“…From 20:48:28 to 20:48:58 UT, sequential chromospheric brightenings (Balasubramaniam et al 2005) were observed to "propagate" westward within a narrow corridor (Figure 1(a), see also the accompanying animation). These were network points (marked by arrows) that suddenly brightened ahead of the Moreton wavefront (marked by "+" symbols).…”
Section: Wave Onset and Propagationmentioning
confidence: 99%
“…1), between 20:41 and 20:43 UT. According to Balasubramaniam et al (2005), SCBs are progression signatures of a coronal mass ejection (CME) that are visible in the chromosphere, at footpoints of magnetic field lines that extend into the corona.…”
Section: Spatial Characteristics Of the Moreton Wavementioning
confidence: 99%
“…In a study of coronal waves related to explosive events, Warmuth et al (2005) mention that this event is accompanied by coronal waves seen in H , SOHO EIT, soft X-rays, and He i measurements, and that the Moreton wave for this event has both northward and southward components. Recently, Liu et al (2006) have reported on the relationship between remote brightenings (also known as sequential chromospheric brightenings [SCBs]; e.g., see Balasubramaniam et al 2005) related to this event and the accompanying CME, flare, and Moreton waves. Therein, Liu et al speculate on the possible magnetic connections between the remote brightenings and the flaring region.…”
Section: Introductionmentioning
confidence: 99%